Evaluation of HIV testing recommendations in specialty guidelines for the management of HIV indicator conditions. Issue 4 (18th August 2016) - Lord, E; Stockdale, AJ; Malek, R; Rae, C; Sperle, I; Raben, D; Freedman, A; Churchill, D; Lundgren, J; Sullivan, AK
Abstract : Objectives: European guidelines recommend HIV testing for individuals presenting with indicator conditions (ICs) including AIDS‐defining conditions (ADCs). The extent to which non‐HIV specialty guidelines recommend HIV testing in ICs and ADCs is unknown. Our aim was to pilot a methodology in the UK to review specialty guidelines and ascertain if HIV was discussed and testing recommended. Methods: UK and European HIV testing guidelines were reviewed to produce a list of 25 ADCs and 49 ICs. UK guidelines for these conditions were identified from searches of the websites of specialist societies, the National Institute of Clinical Excellence (NICE) website, the NICE Clinical Knowledge Summaries (CKS) website, the Scottish Intercollegiate Guidance Network (SIGN) website and the British Medical Journal Best Practice database and from Google searches. Results: We identified guidelines for 12 of 25 ADCs (48%) and 36 of 49 (73%) ICs. In total, 78 guidelines were reviewed (range 0–13 per condition). HIV testing was recommended in six of 17 ADC guidelines (35%) and 24 of 61 IC guidelines (39%). At least one guideline recommended HIV testing for six of 25 ADCs (24%) and 16 of 49 ICs (33%). There was no association between recommendation to test and publication year ( P = 0.62). Conclusions: The majority of guidelines for ICs do not recommend testing. Clinicians managing ICs may be unaware of recommendations produced by HIV societies or the prevalence of undiagnosed HIV infection among these patients. We are piloting methods to engage with guideline development groups to ensure that patients diagnosed with ICs/ADCs are tested for HIV. We then plan to apply our methodology in other European settings as part of the Optimising Testing and Linkage to Care for HIV across Europe (OptTEST) project.